Exploring the effects of global value chain participation, technological eco-innovation and natural resource rents on environmental quality in the EU-14 - Mustafa Necati Çoban; Ömer Faruk Biçen; Abdelmohsen A. Nassani; Muhammad Khalid Anser (Scientific Reports)
Abstract Countries’ participation in the global value chain is significant since it offers them economic benefits. However, the sustainability of life on Earth depends on figuring out how participation in the global value chain affects the environment. Therefore, examining the environmental effects of participation in the global value chain is crucial for the formation, development, or modification of policies concerning nations’ participation in the global value chain. This study aims to examine the influence of variables such as participation in global value chains, technological eco-innovation, natural resource rents, GDP, and population growth on the degradation of the environment in the EU-14 nations. Indicators of environmental deterioration in the research included carbon emissions and ecological footprint. Data on population growth, economic development, carbon emissions, and natural resource rents were all taken from the World Bank database and utilized in the research. Data on ecological footprints, global value chain involvement, and technical eco-innovation were gathered from the Global Footprint Network, the UIBE GVC Laboratory, and the OECD database, respectively. The MMQR approach was used in the research to analyze yearly data for EU-14 nations spanning the years 2007–2021. KRLS and Driscoll-Kraay techniques were also used in the research to assess robustness. The findings indicate that participation in the global value chain across EU-14 nations leads to a decrease in carbon emissions and ecological footprint, resulting in enhanced environmental quality within these countries. Once again, research indicates that in EU-14 nations, technological eco-innovation lowers carbon emissions and ecological footprint. At all quantile levels, it is also discovered that natural resource rents raise carbon emissions and ecological footprint. Additionally, it was discovered that the outcomes of the robustness test agreed with the conclusions drawn. According to the study’s findings, the EU-14 countries should give priority to eco-friendly value chain management techniques in order to maintain environmental quality.